BEYOND SUBSISTENCE: ADVANCING RURAL POULTRY FOR ECONOMIC EMPOWERMENT IN TOBA TEK SINGH (Pakistan Journal of Science, 2025)
This study was planned to look at the influence of rural poultry farming on poverty reduction in Tehsil Toba Tek Singh that involved 302 farmers from 35 villages and. The majority of farmers used backyard poultry for both food and revenue, raising 10–40 birds per household. The results showed that farmers were between the ages of 36 and 40 on average. Thirty percent passed the matriculation exam, while forty-six percent had less than ten years of education. It was observed that 263 farmers (87.1%) came from low-income group and 46% of the poultry care and management was done by women and children. While there was a positive association between financial status and education level (0.205), family size and education level (0.071), and family size and financial status (0.032), the study found a negative correlation between age and education level (-0.159).The birds kept in study area produced just 39 eggs annually and were late to lay their first egg (6.75 months). Hatchability was 69% and the average egg weight was 39 grammes. Poultry birds cost an average of 819.2 ± 59.80 PKR per year, housing cost 952.5 ± 92.93 PKR, feed cost 1111.6 ± 142.30, immunisation cost 168.5 ± 15.42, and treatment cost PKR 508.3 ± 31.81 respectively. There was no funding allocated for sanitising rural poultry housing and biosecurity, and very little was spent on vaccination. Egg sales generated average revenue of 9742.2 ± 674.17 PKR/year, making 95% of total revenue. Poultry farming generated an average yearly profit of 6438 PKR. Less activity (77%), off-feed (57%), feather loss (6%), diarrhoea (55%), blood in the faeces (9%), and trouble breathing (13%), were the most prevalent illness signs seen. Only Newcastle Disease was vaccinated, and 72.6% of farmers vaccinated their chickens. Sanitation practices were not followed, despite farmers adopting preventative measures such adequate housing (64.9%), immunisation (72.6%), and correct diet (66.3%). Dogs (40.9%), snakes (21.2%), rats (8.3%), cats (7.9%), and foxes (9.2%) were the most common predators. Predation was the main cause of disease outbreaks (23.5%) and poultry deaths caused due to predation was (75.8%). Due to unorganized marketing structure, farmers did not receive premium pricing for their rural poultry and the products. A lack of a marketplace (65.2%), fluctuating pricing (49.3%), erratic demand (40.6%), and the involvement of intermediaries (20.5%), expensive transportation (20.1%), and a lack of money (4.3%) were among the issues encountered when marketing. Farmers looked to NGOs for support in order to enhance the rural poultry industry because there were no loans available for poultry production.
Keywords: Rural Poultry; Livelihood, Poverty Alleviation; Subsistence, Punjab